No Steel Band Without the Pan Tuner - Allette, Bert (Newsday)
Andy Neils has been training a new generation of pan tuners under the auspices of Pan Development Unlimited, an organization committed to the development of the art form to ensure that there is a continuity of skills. Pan tuners are essential to cut, hammer and fine-tune the steelpan instrument. the stages of making a tenor pan is also outlined in the article.
Keywords: Steel drum (Musical instrument) -- Tuning -- Trinidad and Tobago; Steel bands (Music) -- Trinidad and Tobago; Steel band music -- Trinidad and Tobago; Steel drum (Musical instrument) -- Instruction and study -- Trinidad and Tobago